Exploring miniaturized EEG electrodes for brain‐computer interfaces. An EEG you do not see?. Issue 4 (6th April 2015) - Bleichner, Martin G.; Lundbeck, Micha; Selisky, Matthias; Minow, Falk; Jäger, Manuela; Emkes, Reiner; Debener, Stefan; De Vos, Maarten
Abstract Electroencephalography (EEG) allows the study of the brain–behavior relationship in humans. Most of what we have learned with EEG was through observing the brain–behavior relationship under well‐controlled laboratory conditions. However, by reducing "normal" behavior to a minimum the ecological validity of the results can be limited. Recent developments toward mobile EEG solutions allow to study the brain–behavior relationship outside the laboratory in more natural situations. Besides mobility and robustness with respect to motion, mobile EEG systems should also interfere as little as possible with the participant's behavior. For example, natural interaction with other people could be hindered when it is obvious that a participant wears an EEG cap. This study evaluates the signal quality obtained with an unobtrusive solution for EEG monitoring through the integration of miniaturized EEG ton‐electrodes into both a discreet baseball cap and an individualized ear piece. We show that such mini electrodes located at scalp and ear locations can reliably record event related potentials in a P300 brain–computer–interface application.